Scientific Committee on Antarctic Research - Kennicutt, Mahlon C. (Ohio State University, 2007)
The media can be accessed here: http://streaming.osu.edu/knowledgebank/042707.mp4 Introduction (00:00:00-00:04:50) -- Presentation(00:04:51-00:54:46)